PENGELOLAAN ASET DESA DI DAERAH RELOKASI BENCANA (Studi Antropologi Pembangunan tentang Pengelolaan Aset Desa-Desa Terdampak Erupsi Gunung Sinabung di Tanah Karo) - Rina Yusdarifa (Aceh Anthropological Journal, 2019)
This study examines about "Management of Village Assets in Disaster Relocation Areas (Development Anthropology Study of Asset Management in Villages Affected by Volcano Eruption in Siosar, Tanah Karo District)". This research uses a descriptive qualitative approach. In dissecting this research, the researcher uses the ethnographic method by presenting a report of the research results in written form. The results showed that the management of village assets in the Siosar relocation area was divided into two categories. Firstly, village assets are managed by each village's government and involving the community such as houses, jambur, BUMDes, agricultural land and others. Secondly, the village managed assets are shared by the three villages in the area of relocation Siosar like, worship places, clean water sources, schools, etc. The results also showed that the obstacles faced by the community of each village in the Siosar relocation area tend to be almost the same as, the source of human resources is not adequate and tend to reject new things, their differences of opinion between the village government in managing village assets, the limitation of area after being relocated, and the lack of assistance from the government. The results also showed that the community of each village in Siosar had a role in managing village assets according to their duties or tasks assigned to them.